2019
DOI: 10.1016/j.dyepig.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of symmetrical pentamethine cyanine dyes as NIR photosensitizers for PDT

Abstract: Herein, we report the synthesis and spectroscopic characterization of novel Near Infra-Red (NIR) pentamethine cyanine dyes, as potential photosensitizers for Photodynamic Therapy (PDT) characterized by a strong absorption in the tissue transparency window (600-800 nm). The heteroaromatic benzoindolenine ring of various symmetrical cyanine dyes has been differently functionalized and quaternarized as a result of a structure-activity study and to determine the substituent effect on the cellular uptake, ROS produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Although some PDT photosensitizers are already commercially available, mostly derived from porphyrins, these light-sensitive molecules have the disadvantage of being slowly eliminated from the body, causing skin photosensitivity [8,39]. Thus, several research studies have recently reported the discovery of new compounds, such as cyanines [40], squaraines [24], chlorins [41] or phthalocyanines [42] which, by appropriate structural modifications, can ideally override the gaps of first-generation photosensitizers [43].…”
Section: Introductionmentioning
confidence: 99%
“…Although some PDT photosensitizers are already commercially available, mostly derived from porphyrins, these light-sensitive molecules have the disadvantage of being slowly eliminated from the body, causing skin photosensitivity [8,39]. Thus, several research studies have recently reported the discovery of new compounds, such as cyanines [40], squaraines [24], chlorins [41] or phthalocyanines [42] which, by appropriate structural modifications, can ideally override the gaps of first-generation photosensitizers [43].…”
Section: Introductionmentioning
confidence: 99%
“…It has a high photoluminescence quantum yield (PLQY) of 47%, which makes this class of cyanine dyes also attractive for NIR fluorescent labeling. 54 56 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Among these three dyes, the Br-substituted one was able to enhance the singlet oxygen quantum yield showing a better half maxima Inhibitory Concentration IC 50 and higher phototoxicity against MCF-7 cells with mitochondria localization. Our group reported a series of symmetrical Cy5 based on the benzoindolenine ring with different substitutions: bromine and C2 or C4 alkyl chains (5d-g) [60]. These PSs have an absorption slightly more shifted toward the NIR (680-699 nm) with phototoxicity at very low concentration (10 nM).…”
Section: Pentamethine Cyanine Dyesmentioning
confidence: 99%